Excessive Volatility in Capital Flows: A Pigouvian Taxation Approach - Jeanne, Olivier; Korinek, Anton (American Economic Review, 2010)
This paper analyzes prudential controls on capital flows to emerging markets from the perspective of a Pigouvian tax that addresses externalities associated with the deleveraging cycle. It presents a model in which restricting capital inflows during boom times reduces the potential outflows during busts. This mitigates the feedback effects of deleveraging episodes, when tightening financial constraints on borrowers and collapsing prices for collateral assets have mutually reinforcing effects. In our model, capital controls reduce macroeconomic volatility and increase standard measures of consumer welfare.